2020
DOI: 10.1101/2020.03.06.979583
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adhesion-mediated mechanosignaling forces mitohormesis

Abstract: Mitochondria control eukaryotic cell fate by producing the energy needed to support life and the signals required to execute programmed cell death. The biochemical milieu regulates mitochondrial function and contributes to the dysfunctional mitochondrial phenotypes implicated in cancer and the morbidities of ageing. Extracellular matrix stiffness and cytoskeletal tension are also altered in cancer and in aged tissues. We 5 determined that cytoskeletal tension elicits a mitochondrial stress response that modifi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 114 publications
(53 reference statements)
5
14
0
Order By: Relevance
“…A recent study found that hyperactivation of integrin signaling through several paradigms (growth on increased stiffness, constitutive active 1 integrin, hyperglycemia, etc.) results in mitochondrial fragmentation and robust UPR MT activation through cytoskeletal remodeling (14). Consistent with these findings, we find that overexpression of 1 integrin in mammalian cells is sufficient to cause mitochondrial fragmentation and induce canonical UPR MT targets (fig.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…A recent study found that hyperactivation of integrin signaling through several paradigms (growth on increased stiffness, constitutive active 1 integrin, hyperglycemia, etc.) results in mitochondrial fragmentation and robust UPR MT activation through cytoskeletal remodeling (14). Consistent with these findings, we find that overexpression of 1 integrin in mammalian cells is sufficient to cause mitochondrial fragmentation and induce canonical UPR MT targets (fig.…”
Section: Resultssupporting
confidence: 87%
“…Consistent with previous findings (39), we find that knockdown of a select few genes that induce UPR MT and therefore likely cause mitochondrial stress also affects the cytosolic HSR. It is likely that under conditions of mitochondrial stress, HSF-1 (heat-shock factor 1) can be mobilized to affect targets of the cytosolic HSR to improve organismal homeostasis (14,39,40). RNAi knockdown of most of our candidate genes failed to induce the HSR, and all failed to induce the UPR ER , suggesting that our screening paradigm was highly specific in identifying genes involved in mitochondrial homeostasis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations